Base nacional comum curricular e educação escolar de adolescentes: uma análise à luz da pedagogia histórico-crítica e da psicologia histórico-cultural - TOMAZIN, Silvio Santos (2020)
This work is linked to the research line 1: Public Policies in Education, Training Processes and Diversity of the Graduate Program in Education (PPGE) - Master’s and Doctorate, of UNOESTE, Campus de Presidente Prudente, SP. Based on a theoretical-conceptual and documentary research, based on the assumptions of historical-critical pedagogy and historical-cultural psychology, this dissertation aimed to analyze the limits of a teaching aligned with the new National Common Curriculum Base (BNCC) concerning the psychic development of high school adolescents. The study showed that an education planning aligned with BNCC does not allow full development in adolescence. The arguments used to defend the above hypothesis were taken from the critical analysis, whose results were as follows: a) an education centered on the student, which dichotomizes the teacher-student relationship, is unilateral and not integral; b) a skills development education is based on doing, so it is a unilateral education that dichotomizes theory and practice; c) an education that forms the adolescent simply for the labor market cannot be considered integral, but, yes, unilateral; d) an education that dichotomizes form and content in the development process in adolescence cannot be considered an integral education. In view of the analysis, the work presents the historical-cultural conception of adolescence as a contribution to the definition of the curriculum regarding school education in this stage of human development.